Assessing rangeland cover conversion in Jordan after the Arab spring using a remote sensing approach. (October 2018) - Sawalhah, Mohammed N.; Al-Kofahi, Salman D.; Othman, Yahia A.; Cibils, Andres F.
Abstract: The influence of population growth and Syrian refugee settlements on rangeland degradation in Jordan using remotely-sensed data was assessed. Eleven cloud-free Landsat 8 Operational Land Imager (OLI) Images that cover the study area were used. Maximum likelihood classifier was applied to estimate rangeland, cropland, urban, water and forest cover percentages over the study area for the period 2013–2015. Change detection analysis of both 2013 and 2015 images revealed a dramatic expansion of urban lands and a consequent reduction in rangelands, especially in north-western Jordan. Our analysis suggests that Jordanian rangeland area decreased by 9.6%, forests by 1.5% and water by 0.6% during the study period (2013–2015). Meanwhile, urban lands increased by 11.4% and croplands by 0.2%. We attributed this change mainly to Syrian civil war and refugee settlements. This settlement process increased the demand for food and water and accelerated desertification processes in Jordanian rangelands, especially those in the north-western region. Our study underscores the value of using remotely sensed data as a viable approach to quantify degradation in Middle Eastern rangelands. Overall, we suggest initiating rigorous urban settlement regulations and land conservation control programs to mitigate land degradation in Jordanian rangelands. Highlights: Medium spatial resolution images provide opportunities to map land cover with sufficient accuracy. Temporal and spatial land cover change can be detected using change detection analysis of remotely sensed data. Refugees' settlements could change land use/cover significantly in short time. Syrian conflicts induced water scarcity and food security problems and accelerated the desertification process in Jordan.